Oral Glutamine Supplementation in Dogs Infected with Canine Parvovirus Type 2 - Melo, Alice Madeira Campos [UNESP]; Ghedin, Victoria [UNESP]; Romano, Felipe Saab; dos, Santos Natalia Ribeiro [UNESP]; Pellegri, Lara Alice Pagura [UNESP]; Ichikawa, Ricardo Shoiti [UNESP]; Hussni, Maria Fernanda [UNESP]; Paes, Antonio Carlos [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Rahal, Sheila Canevese [UNESP]; Melchert, Alessandra [UNESP] (Elsevier, 2025)
This study aimed to assess the impact of oral glutamine supplementation in dogs infected with Canine Parvovirus Type 2 (CPV-2). The dogs were randomly divided into two groups: Group 1 (n=10) received glutamine supplementation (500 mg/kg/day), and ad libitum feeding; Group 2 (control) (n=10) received a placebo and ad libitum feeding. Group 1 dogs were significantly younger (mean 3.5 ± 0.5 months) than those in Group 2 (mean 6.3 ± 3.0 months; p=0.036). Data from the two groups were compared at the hospital admission and discharge. No significant differences were observed between groups in body weight, physical examination parameters, body condition score, and muscle condition score at hospital admission. Group 1 had lower albumin levels than Group 2 at the initial assessment. The two groups had no difference in the number of days until the start of spontaneous feeding. No significant differences were observed between the groups regarding days until clinical improvement and duration of hospitalization. However, Group 1 had a shorter duration of diarrhea (mean of 2.4 days) compared to Group 2 (mean of 4.9 days) and a better fecal score, (median 5 in Group 1; median 6.5 in Group 2). In Group 2, mortality was 10% (1 animal), while there were no deaths in Group 1. Glutamine supplementation was beneficial in dogs with CPV-2, reducing the duration of diarrhea and improving fecal score. In conclusion, glutamine shows promise as an adjunctive treatment in the treatment of dogs with CPV-2 and warrants further investigation.